Independent Learning-Independent Campus (MBKM) in Students’ Perception - Putri Ulfa Kamalia; Eka Hendi Andriansyah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This study aims to analyze students’ perception of the technical, process and evaluation learning of the Independent Learning-Independent Campus or Merdeka Belajar-Kampus Merdeka (MBKM). This study is a descriptive with a quantitative approach. The  samples in this study were students of the Economic Education Study Program, Faculty of Economics and Business, Universitas Negeri Surabaya who participated in student exchanges in the Cooperative Economics course. The instrument used is in the form of a questionnaire distributed via google form. The results obtained from this study are: 1) Students’ perception of technical indicators in MBKM learning are positive; they don’t experience signal problems and can access MBKM learning easily; 2) Students’ perception of learning process indicators in MBKM learning on average are positive; students can understand MBKM learning materials through discussions and communication between lecturers and students goes well; 3) Students’ perception of evaluation indicators in MBKM learning on average are positive; students can do midterm and final exam well independently and students are satisfied with the implementation of MBKM learning so they are interested in following it again in the next semester, but students feel that MBKM learning is not optimal because it is done  online.